Foot injuries in dogs and cats - GRIGOROPOULOU (Β. ΓΡΗΓΟΡΟΠΟΥΛΟΥ) V.; PRASSINOS (Ν.Ν. ΠΡΑΣΙΝΟΣ) N. N.; PAPAZOGLOU (Λ.Γ. ΠΑΠΑΖΟΓΛΟΥ) L. G. (Journal of the Hellenic Veterinary Medical Society, 2017)
Paws are very important for weight-bearing and ambulation in small animals. These abilities are highly preserved due to the presence of foot pads on the palmar and plantar surface of the paws. The incidence of distal limb skin injuries is relatively high and these wounds require immediate and meticulous management, especially if there is skin loss. In the later cases, the use of specialized reconstructive surgical techniques makes foot salvage possible, thus avoiding limb amputation, which was the only solution in the past.